Curation of research data in the disciplines of Engineering - Ball, Alex; Neilson, Colin (Digital Curation Centre, 2009)
Case Study produced by the Digital Curation Centre (DCC) SCARP project, funded by the Joint Information Systems Committee (JISC).
Keywords: Digital Curation